Diversifikasi Olahan Ubi Ungu untuk Meningkatkan Daya Saing Produk Pangan di Sleman - Setiyoko, Agus; Putri, Soraya Kusuma; Casmi, Eno (Warta LPM, 2023)
The PKK group from RT 004 Pasekan Lor, Balecatur, Gamping, Sleman, location is approximately 4.8 km from Mercu Buana University, Yogyakarta. One of the food potentials that this group has begun to process is purple sweet potato. Purple sweet potatoes are commonly processed by steaming, boiling, or frying. On the opposite hand, with technology present, purple sweet potatoes can be processed into various food products with high nutritional and economic value. This community-based project desires to improve people's knowledge and expertise in purple sweet potato processing, labeling, and packaging technology to enhance food goods' competitiveness in the PPK RT 004 Pasekan Lor group. This voluntary activity is being done by (1) Counseling on diversification of processed purple sweet potato, (2) Practice and training on making various processed purple sweet potato, (3) Counseling on various types of labels, packaging, and packaging methods, (4) Counseling and practice of online product marketing, (5) Submission of sweet potatoes production tools. According to the evaluation of this community service project results: (1) Members' awareness of the variety of processed purple sweet potatoes grew from 60% to 95%, (2) Skills in product processing rose from 57% to 89%, (3) From 50% to 84% of the population are understanding how to create labels and package food that fits with standards, (4) Understanding and skills in marketing products online increased from 45% to 75%, (5) Partners have production equipment for various processed purple sweet potatoes. Regarding program benefits, 92% of partners considered it very useful, while 85% rated it very easy regarding ease of technology implementation.